Optimization of Peeling Process of Dried ‘Hui’ Jujube and Changes of the Functional Components - Ebrayim AISAJAN; Wenyu ZHENG; Fei WU; Peng CHEN; Cuiyun WU; Hongjin BAI (Shipin gongye ke-ji, 2023)
In this study, Xinjiang dry ‘Hui’ jujube was peeled by lye. The antioxidant activity was evaluated on the scavenging ability on ABTS+ free radicals and iron reducing ability. The changes of metabolites were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The peeling process of dyr ‘Hui’ jujube was optimized through the single-factor experiments response surface experiments based on the quality (i.e. color, flavor, texture, peeling rate), the antioxidant activity and the changes of functional components in the jujube. The optimal conditions were as follows: The concentration of lye was 3%, the peeling time was 3 min, and the speeling temperature was 79 ℃. In comparison, under these process conditions, 99.99% of dried ‘Hui’ jujube were peeled, with the highest sensory score of 80.50±0.50. Compared with before peeling, the total phenol content, soluble solid content, ABTS+ free radical scavenging ability and iron reduction ability of jujube meat after peeling showed a decreasing trend (P<0.05). Up to 968 metabolites were identified by LC-MS/MS. The KEGG enrichment analysis revealed that flavonoids and nucleotides were the main loss functional components during the peeling process. In this study, various methods were used to comprehensively evaluate the peeling technology of jujube with alkali liquor, which provided theoretical basis for further fine processing and production of Xinjiang ‘Hui’ jujube.